PENGARUH FASILITAS KERJA, KONFLIK PERAN, MOTIVASI KERJADAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA TEBING TINGGI - Endar Khairul Daulay (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
The problems in this research are: How is the influence of work facilities, role conflict, work motivation and emotional intelligence partially and concurrently on the performance of employees in the Primary Tax Office Tebing Tinggi? Research objectives: To determine the effect of work facilities, role conflict, motivation and emotional intelligence partially and simultaneously on the performance of employees in the Primary Tax Office Tebing Tinggi. The hypothesis proposed is: There is a significant effect of work facilities, role conflict, work motivation and emotional intelligence partially and jointly on the performance of employees in the Primary Tax Office Tebing Tinggi. The study was conducted at the Pratama Tebing Tinggi Tax Service Office Jalan Sutoyo Number 32 Rambung Tebing Tinggi, with a population of 83 people, and a study sample. of 82 people.Based on the analysis results obtained work facilities have a positive and significant effect on the performance of the Primary Tax Service Office Tebing Tinggi, this is supported by the results of t count analysis t-table (1.953 1.67) at n = 82 at 95% significance level. Role conflict has a negative and significant effect on the performance of the Primary Tax Service Office of Tebing Tinggi, this is supported by an analysis of t count t-table (0.112 ˂ 1.67) at n = 82 at 95% significance level. Work motivation has a positive and significant effect on the performance of the Tebing Tinggi Primary Tax Office employee, this is supported by an analysis of t count t-table (3.53 1.67) at n = 82 with a significant level of 95%. Emotional intelligence has a positive and significant effect on the performance of the Primary Tax Service Office of Tebing Tinggi, this is supported by the results of thitung analysis t-table (4.01 1.67) at n = 82 with a significance level of 95%.Value of F-count F table (138,565 2,48) This states that together (multiple) there are positive and significant effects of work facilities, role conflict, work motivation and emotional intelligence on the performance of employees of the Pratama Tebing Tinggi Tax Office . Thus the hypothesis proposed is accepted by the truth